The Effect of Home Visit Strategy on Reading Comprehension Of the Fifth Grade Students - Hermini Hermini; Sulamseh Sulamseh; Paldy Paldy; Juwita Crestiani (Institut Agama Islam Negeri Palopo, 2022)
This study aims to determine the effect of the home visit strategy on the reading comprehension of the fifth grade students at SDN 188 Manunggal. This research is an ex-post facto research type. The population in this research was 16 students and the sample was taken by totaling sampling. The data were collected by questionnaires and tests. The data analysis technique used in this research is descriptive statistical analysis and inferential statistical analysis. The results shows that there was an effect of the home visit strategy toward the reading comprehension of the fifth grade students of SDN 188 Manunggal, it is indicated by r-count 0.107 < r-table 0.497 with a significance level of 5% and the number N = 16 with a significance value of 0.693 > 0.05. So the alternative hypothesis (H1) is accepted and the hypothesis (H0) is rejected. The level of closeness between the comprehension test and student responses shows that there is an influence by the point 0.600-0.799 on the strong category. It can be concluded that there is a significant effect between the home visit strategy toward the students' reading comprehension of the fifth grade students at SDN 188 Manunggal.